2021
DOI: 10.3389/fphar.2021.699044
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals as Potential Chemopreventive and Chemotherapeutic Agents for Emerging Human Papillomavirus–Driven Head and Neck Cancer: Current Evidence and Future Prospects

Abstract: Head and neck cancer (HNC) usually arises from squamous cells of the upper aerodigestive tract that line the mucosal surface in the head and neck region. In India, HNC is common in males, and it is the sixth most common cancer globally. Conventionally, HNC attributes to the use of alcohol or chewing tobacco. Over the past four decades, portions of human papillomavirus (HPV)-positive HNC are increasing at an alarming rate. Identification based on the etiological factors and molecular signatures demonstrates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 315 publications
(373 reference statements)
0
12
0
Order By: Relevance
“…Morphologically, CSNPs are identified by most studies as spherical particles [ 10 , 69 ]. This study showed that the shape of the NPs of CS–LMW and CS–HMW is spherical, as depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphologically, CSNPs are identified by most studies as spherical particles [ 10 , 69 ]. This study showed that the shape of the NPs of CS–LMW and CS–HMW is spherical, as depicted in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Because amine groups must have a positive charge, the ZP falls with molecular weight. The PDI was higher in all NPs produced with low MW CS than in high MW CS [ 10 , 41 , 51 , 57 , 59 ]. The presence of free amino groups raised the surface charges and ZP of the NPs, strengthening the electrostatic contacts between the NPs and the drug, maintaining the spherical shape of the beads, and decreasing their size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The constitutive activation of JAK/STAT signaling is documented in diverse malignancies and is associated with the transactivation of several genes in malignant cells both in vitro and in vivo settings ( Mali, 2015 ). Increasing STAT3 phosphorylation in primary HNC tumors and normal mucosa from HNC patients indicates early STAT3 activation in carcinogenesis ( Aggarwal et al, 2021 ). Furthermore, a study has been performed and reported the increased STAT3 expression in smokeless tobacco-mediated HNC with minimal STAT3 in normal tissues ( Sinevici and O’sullivan, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomically four main regions included in HNC are, the oral cavity, pharynx, nasal cavity, and larynx. Histologically HNC starts with oral precancerous lesions such as, leukoplakia, erythroplakia, and oral submucous fibrosis and malignant tumors like squamous cell carcinoma, adenocarcinoma, lymphoma, and blastoma (Aggarwal et al 2021). Depending on etiological factors HNC can be tobacco‐induced (Pipes, cigarettes, and cigars), alcohol‐induced, or Virus (Human‐papillomavirus and Epstein‐Bar virus) mediated (Hashibe et al 2009).…”
Section: Introductionmentioning
confidence: 99%